2016
DOI: 10.4236/ojmi.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Imaging for Magnetic Hyperthermia Treatment: Visualization and Quantification of the Intratumoral Distribution and Temporal Change of Magnetic Nanoparticles <i>in Vivo</i>

Abstract: Purpose: Magnetic hyperthermia treatment (MHT) is a strategy for cancer therapy using the temperature rise of magnetic nanoparticles (MNPs) under an alternating magnetic field (AMF). Recently, a new imaging method called magnetic particle imaging (MPI) has been introduced. MPI allows imaging of the spatial distribution of MNPs. The purpose of this study was to investigate the feasibility of visualizing and quantifying the intratumoral distribution and temporal change of MNPs and predicting the therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…were measured with a caliper every day and the tumor volume (V) was calcu- After the MPI studies, we drew a region of interest (ROI) on the tumor in the MPI image ( Figure 2) and calculated the average and maximum MPI values in the same manner as that in our previous papers [14] [15]. We also calculated the number of pixels within the ROI and then calculated the total MPI value from the product of the average MPI value and the number of pixels.…”
Section: Data and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…were measured with a caliper every day and the tumor volume (V) was calcu- After the MPI studies, we drew a region of interest (ROI) on the tumor in the MPI image ( Figure 2) and calculated the average and maximum MPI values in the same manner as that in our previous papers [14] [15]. We also calculated the number of pixels within the ROI and then calculated the total MPI value from the product of the average MPI value and the number of pixels.…”
Section: Data and Statistical Analysesmentioning
confidence: 99%
“…MPI is capable of imaging the spatial distribution of MNPs in positive contrast without any background and with high sensitivity and spatial resolution [11]. We recently have developed an MPI scanner based on the field-free-line encoding scheme [12] [13] and succeeded in Open Journal of Applied Sciences imaging the intratumoral distribution of MNPs and quantifying its temporal change in vivo [14] [15]. We also showed that MPI is useful for predicting the therapeutic effect of MHT [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the cytotoxicity of CDDP increases linearly with increasing temperature when combined with hyperthermia 25) . We previously reported that the temperature in a tumor increased after the start of MHT and reached a higher temperature with increasing concentration of MNPs 26) . Thus, it is expected that the therapeutic effect of CDDP increases with increasing concentration of MNPs in the tumor or the dose of CDDP can be reduced when combined with MHT.…”
Section: Therapeutic Effectmentioning
confidence: 91%
“…Among the magnetic materials for biomedical applications, superparamagnetic nanoparticles have been gaining more attention due to their potential as not only therapeutic agents for magnetic hyperthermia but also as diagnostic agents for magnetic particle imaging, which has been proposed to visualize the spatial distribution of superparamagnetic nanoparticles recently . So far, a MRI contrast agent named Resovist® that is clinically approved for human use has been widely used to evaluate magnetic hyperthermia and/or magnetic particle imaging applications . To the best of our knowledge, there is little or no information on its heating property dependence on the applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%